Genoese financiers and the redistribution of Spanish bullion: The "Mediterranean Road" (1630-1700) - Claudio Marsilio (The Journal of European Economic History (JEEH), 2021)
Classical historiography treats the years 1650-1700 as pivotal in the movement of the centre of international finance first to Amsterdam and then, at the beginning of the 18th century, to London. The Mediterranean Sea, as theorised by Fernanc Braudel's "world-economy" model, was relegated to a secondary role, while the destiny of the international economy was decided in northern Europe. Many works have examined the role of the Genoese bankers in a previous period (1550-1650). After the bankruptcy of Philip IV (1627), however, we get the impression that Genoa disappeared from the map of European finance. What happened to the Genoese brokers between 1650 and 1700? Their proverbial expertise and financial intuition allowed them rapidly to change course and undertake a strategy which took the form of an intelligent and utilitarian "reconversion." Starting from the 1630s, the GEnoese bankers sought to obtain repayment in silver of the capital they had invested in Madrid. This fresh inflow of capital gave the new generation of Genoese bankers the opportunity for a radical change of perspective. They would no longer be active in the market for Spanish public debt and loans (asientos); instead, they would manage financial services and the international bullion market. This article shows how the Genoese bankers played a pre-eminent role on the bullion marke throughout the second half of the 17th century.
Keywords: 330